History Education and the Young Generation: Exploring National Values in the Indonesian Education Curriculum - Burhanuddin Burhanuddin; Bruce VanSledright (Universitas Negeri Malang, 2024)
In the context of globalization, it is crucial to cultivate a sense of nationalism and historical awareness among learners. The inculcation of nationalistic values can serve as a means of fostering a national character that aligns with the nation's identity. Character education represents an initiative undertaken by educational institutions to influence, direct, and guide the conduct of students in alignment with the values espoused by specific norms, with the aim of mitigating the adverse effects of the globalizing era. One of the adverse effects is that the younger generation's interest in their own culture has begun to wane, leading to a shift in values in both personal and social life. It can be reasonably argued that there is a significant, positive influence of history education on the attitude of nationalism in students. Indeed, it could be proposed that the attitude of nationalism can be explained and influenced by history education, given that history learning provides material about the values of nationalism so that students are able to understand this value. This evidence suggests that history education plays an important role in shaping the attitude of nationalism among students.